METHODOLOGY FOR DEVELOPING CREATIVE COMPETENCE IN FUTURE “TECHNOLOGY” SUBJECT TEACHERS FOR PROFESSIONAL ACTIVITY - Avazov G'oyibnazar Berdiyevich (Modern American Journals, 2025)
This article presents a methodology for developing creative competence in preparing future “Technology” subject teachers for professional activity. This methodology supports teachers in demonstrating a creative approach in the field of technology and in discovering, developing, and applying new strategies in practice. Integrating technological innovations and scientific methods helps foster teacher creativity and solve logical problems.
Keywords: Educational system, technological education, information and communication technologies, qualified personnel, digital education, creativity.